Imbuing the Supply Chain with the Customers Mind: Todays Reality, Tomorrows Opportunity - Moskowitz, Howard; Gere, Attila; Moskowitz, Yeshaya Danny; Sherman, Robert; Deitel, Yehoshua; Nagarajan, Divya; Papajorgji, Petraq (Edelweiss Applied Science and Technology, 2019)
This paper introduces a new approach to understanding the mind of the customer with the goal of optimizing the supply chain by creating, marketing and then delivering what the customer(s) want. The underlying notion is that for every product one can discover groups of people with defined preferences for the product and defined messages which drive expected purchase. The approach divides into two parts, knowledge development through Mind Genomics experiments and mind-set sequencing through the PVI (Personal Viewpoint Identifier). The paper shows data for six flavored beverages, the creation of mind-sets and the creation of the PVI to drive the messaging and thus purchase of each product. The paper finishes with the prospects for the world of product design and marketing when one can rapidly discover these product-specific mindsets and the messages which excite each mind-set.